Staging Black Fugitivity - McCormick, Stacie Selmon (Black performance and cultural criticism., 2019)
"Argues that contemporary black dramas use the slave past to complicate views of the history of slavery, the realities of racial progress, and black subjectivity. McCormick analyzes work by August Wilson, Suzan-Lori Parks, Tanya Barfield, Lorraine Hansberry, Lydia Diamond, Robert O'Hara, and Branden Jacobs-Jenkins, amongst others"--